Correlation between Surface Tension and the Bulk Dynamics in Salty Atmospheric Aquatic Droplets - Salameh, Anastasia; Vorka, Flora; Daskalakis, Vangelis (My University, 2016)
The properties of the liquid-gas interface in the presence of surface-active organic matter, and the bulk response to changes of the resulting surface tension are key factors in assessing cloud microphysics or condensation/evaporation dynamics for atmospheric particles. A fundamental question rises on how we can induce changes in the bulk of an aquatic droplet by varying its surface-activity. The challenging aspect of answering such a question rises from the fact that water exerts complexity in its interactions giving rise to many anomalous properties. Here, we employ molecular dynamics simulations on salty aquatic droplets, associated with new particle formation in the atmosphere. We present a correlation between surface tension and a bulk property like the static dielectric constant, which is closely related to the water activity in Köhler theory of droplet formation and growth. We thus correlate surface to bulk properties. The particles we probe consist of water, salt (ammonium bisulfate), and surface-active organic matter. A particularly useful result of our study is that surface-active organic matter on the surface of a salty droplet can alter the solvent properties of water in terms of water orientation/water activity measured by the static dielectric constant in the bulk.
Keywords: Atmospheric aquatic droplets; Water